INTERAKSI DAN DINAMIKA KOMUNIKASI KELOMPOK VIRTUAL DALAM KOMUNITAS GAME PLAYERUKNOWN’S BATTLEGROUNDS: PERSPEKTIF SOSIOLOGI KOMUNIKASI - Muhammad Farhan Alamsyah (Prodi Sosiologi FISIP UPR, 2025)
This study analyzes the interactions and dynamics of virtual group communication within the community of PlayerUnknown's Battlegrounds (PUBG) Mobile players from the perspective of communication sociology. The research focuses on how digital communication shapes teamwork patterns, negotiation, and decision-making processes, as well as the role of in-game symbols in forming social identity and group hierarchy. Using a descriptive qualitative approach, data were collected through interviews and literature review. This study integrates Herbert Blumer's Symbolic Interactionism Theory and Anthony Giddens' Structuration Theory to understand how group norms and symbols, such as nicknames, ranks, and in-game achievements, influence social dynamics in virtual communities. The findings reveal that these symbols not only reflect social status but also establish dynamic group norms. The social structures within the PUBG community are flexible, shaped by player interactions, and contribute to team solidarity. This study provides insights into how virtual spaces, such as PUBG Mobile, serve as platforms for building social identity and fostering complex cooperation, while also revealing the implications of digital communication on group dynamics in real-world contexts.